Robust static output feedback H∞-controller design for three degree of freedom integrated bus lateral, yaw, roll dynamics model - Altork, Basim; Yazici, Hakan (SAGE PUBLICATIONS LTD, 2019)
In this paper, a three-degree-of freedom (3 DOF) integrated vehicle lateral, yaw, roll dynamics model with optimal control design have been proposed to improve the bus lateral stability and handling performance. First, a 3 DOF vehicle model for a passenger bus is introduced. The 3 DOF model dynamics include the vehicle steering wheel angle, forward speed, yaw motion, sideslip angle, lateral acceleration and the rolling motion. Then, the presented 3 DOF model is used to design the robust static output feedback H infinity controller for both nominal system and uncertain system. The proposed controller is designed to improve the bus lateral stability and handling performance by controlling the yaw rate during normal driving and maneuvers. For the robust static output feedback H infinity controller, the norm bounded uncertainty is considered to simulate the variation of vehicle forward velocity uncertainty. The robust controller is designed to check the lateral stability of the bus at different forward velocity and at different velocity uncertainty. The controllers are synthesized within the H infinity control approach and the controllers' design conditions are given within the Linear Matrix Inequalities (LMIs) framework. Numerical simulations have been carried out to demonstrate the effectiveness of the proposed controllers. The obtained simulation results show that the designed nominal and robust controllers enhance the lateral stability of the bus by reducing the amplitude of the yaw rate, lateral acceleration and rolling motion. Hence, the improvements in bus lateral stability and handling performance are achieved.
Keywords: Static output feedback H-infinity control; integrated 3 DOF bus model; yaw rate stability; norm-bounded uncertainties; attenuation disturbance level; linear matrix inequalities; SYSTEMS; Automation & Control Systems; Instruments & Instrumentation